Evaluation of GENESIS-BCPTM Scaffold Composed of Hydroxyapatite and β-Tricalcium Phosphate on Bone Formation - 양대혁; 권일근; 박하나; 배민수; 이정복; 허동녕; 이원준; 박영민; 조영환; 김덕수 (Macromolecular research, 2012)
The purpose of this study was to evaluate the effects of a GENESIS-BCPTM scaffold composed of hydroxyapatite (HAp) and β-tricalcium phosphate (β-TCP) on bone formation. The rela tive ratio of components forming GENESIS-BCPTM was investigated by confirming the molar ratio of Ca/P through energy dispersive spectrometer (EDS) analysis. The results being that the scaffold is comprised of 60% HAp and 40% β-TCP. Moreover,scanning electron microscopy (SEM) images showed a unique surface morphology similar to a soccer ball. X-ray diffraction (XRD) analysis showed that the porosity, crystallinity, and Ca/P ratio were 65.5%, 84.9%, and 1.61%,respectively. In vitro tests including cytotoxicity and cell proliferation showed a good biocompatibility of GENESIS-BCPTM. In vivo tests, including mouse skull test, and hematoxylin and eosin stains of GENESIS-BCPTM implanted in rabbit and human subjects showed that the bone graft is effective to accelerate new bone formation. It was concluded that GENESIS-BCPTM can be used as an effective alloplast bone graft. KCI Citation Count: 6